Core temperature responses to cold-water immersion recovery: A pooled-data analysis - Stephens, J. M.; Sharpe, K.; Gore, C.; Miller, J.; Slater, G. J.; Versey, N.; Peiffer, J.; Duffield, R.; Minett, G. M.; Crampton, D.; Dunne, A.; Askew, C. D.; et al. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the effect of postexercise cold-water immersion (CWI) protocols, compared with control (CON), on the magnitude and time course of core temperature (Tc) responses. Methods: Pooled-data analyses were used to examine the Tc responses of 157 subjects from previous postexercise CWI trials in the authors` laboratories. CWI protocols varied with different combinations of temperature, duration, immersion depth, and mode (continuous vs intermittent). Tc was examined as a double difference (Tc), calculated as the change in Tc in CWI condition minus the corresponding change in CON. The effect of CWI on Tc was assessed using separate linear mixed models across 2 time components (component 1, immersion; component 2, postintervention). Results: Intermittent CWI resulted in a mean decrease in Tc that was 0.25°C (0.10°C) (estimate [SE]) greater than continuous CWI during the immersion component (P=.02). There was a significant effect of CWI temperature during the immersion component (P=.05), where reductions in water temperature of 1°C resulted in decreases in Tc of 0.03°C (0.01°C). Similarly, the effect of CWI duration was significant during the immersion component (P=.01), where every 1 min of immersion resulted in a decrease in Tc of 0.02°C (0.01°C). The peak difference in Tc between the CWI and CON interventions during the postimmersion component occurred at 60 min postintervention. Conclusions: Variations in CWI mode, duration, and temperature may have a significant effect on the extent of change in Tc. Careful consideration should be given to determine the optimal amount of core cooling before deciding which combination of protocol factors to prescribe.